2019
DOI: 10.3389/fevo.2019.00385
|View full text |Cite
|
Sign up to set email alerts
|

Unclear Intentions: Eavesdropping in Microbial and Plant Systems

Abstract: Eavesdropping, the interception of signals by unintended receivers, is an important component of the ecology and evolution of communication systems. Plants and microbes have complex communication systems with important consequences for agriculture, human health, and ecosystem functioning. Eavesdropping, however, has mostly been studied in animal systems. In this review, we argue that eavesdropping is an important force shaping the ecology and evolution of communication in these non-animal systems. To date, stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 118 publications
0
15
0
Order By: Relevance
“…This demonstrates that changes in susceptibility in intraspecific plant mixtures does not require inoculation of the neighbour, and thus does not depend on the neighbour's susceptiblity level, and hence expression of immunity can be constitutive. In that respect, NMS does not resemble the many cases of 'eavesdropping' situations reported so far (Rebolleda-Gómez and Wood, 2019). (A) Plants of the wheat genotype Cultur were grown either with itself (CUL-CUL, 'pure' condition) or with the genotype Atoudur (CUL-ATO) and were inoculated with Puccinia triticina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrates that changes in susceptibility in intraspecific plant mixtures does not require inoculation of the neighbour, and thus does not depend on the neighbour's susceptiblity level, and hence expression of immunity can be constitutive. In that respect, NMS does not resemble the many cases of 'eavesdropping' situations reported so far (Rebolleda-Gómez and Wood, 2019). (A) Plants of the wheat genotype Cultur were grown either with itself (CUL-CUL, 'pure' condition) or with the genotype Atoudur (CUL-ATO) and were inoculated with Puccinia triticina.…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown in both inter-and intra-specific plant-plant interactions, in particular against insects (Karban et al, 2000(Karban et al, , 2006. In the case of intraspecific interactions, such a phenomenon is called 'eavesdropping' (Rebolleda-Gómez and Wood, 2019) where a previously unaffected plant primes its defenses after perceiving a signal emitted by the neighbouring, attacked plant. While there are many report that sick or attacked plants can signal danger to neighbours, thus triggering their immunity and reducing their susceptibility (Cheol Song et al, 2016;Wenig et al, 2019), very few studies have indicated that heathy plants can directly affect immunity in their plant neighbourhood.…”
Section: Introductionmentioning
confidence: 99%
“…The signalling molecules called autoinducers that accumulate in the environment in a density-dependent way are not synthesized by certain mutants called signal blind mutants that use the autoinducers without having the cost of signal production; they thus have an advantage. Signals can be intercepted by unintended receivers; 27 in such a mechanism, termed eavesdropping, the signaler benefits from its signal that reaches the intended receiver as expected, but it has to pay the fitness cost when the signal secreted is intercepted by an eavesdropper. This mechanism is considered to have both ecological and evolutionary significance.…”
Section: Social Interactions In Microbial Communitiesmentioning
confidence: 99%
“…Plants have the ability to pick up on above-and below-ground cues from neighboring plants about potential threats, such as herbivory or drought, and use them to induce defensive responses before exposure to stress occurs (Karban et al, 2003;Engelberth et al, 2004;Kessler et al, 2006;Falik et al, 2011). The majority of work on plant eavesdropping has been done on herbivore-induced plant volatiles, but signals emitted by roots and microbes in the soil have also been studied (Falik et al, 2011;Morrell and Kessler, 2014;Blande, 2017;Rebolleda-Gómez and Wood, 2019). When plants are damaged, the composition of their volatiles change and can serve as reliable signals of impending pest presence.…”
Section: Asymmetrical Anticipatory Regulationmentioning
confidence: 99%